PENERAPAN METODE GREEN SUPPLY CHAIN OPERATION REFERENCE (GSCOR) PADA PENGOLAHAN RIBBED SMOKE SHEET (RSS) (Studi Kasus Di PTPN XII Sumber Tengah Silo, Jember) - Ida Bagus Suryaningrat; Erina Rezky A; Elida Novita (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
This research was conducted in a case study of a rubber processing factory involving several parts, namely gardens, processing plants, and final processing. In the last 2 years, the company has started with the implementation of green supply chain management program included the waste treatment system and recycle of solid and liquid waste. Therefore it was necessary to evaluate and measure the performance of the green supply chain to find out how well the performance of the company's supply chain. The purpose of this study was to measure the performance of the green supply chain in the processing of Ribbed Smoke Sheet (RSS) by using the application of Green Supply Chain Operation Reference (SCOR) method. This study employed the model Green Supply Chain Operations Reference (Green SCOR) and Analytical Hierarchy Process (AHP) method. Data collection was reached through interview and questionnaire techniques to the experts. The Green SCOR model was implemented to design business processes and measure performance using the Key Performance Indicator (KPI). The AHP method was required to reach weight and rank to each indicators used in this study. This study employed 24 KPIs to measure the performance of the company's supply chain. Performance value of green supply chain in the company has a value of 72.03% which was classified into good level. Another low score indicators was used as a basic to develop proposed recommendations for company’s green supply chain improvement program